PEMAKAIAN AKRONIM DI LINGKUNGAN PEMERINTAH KOTA SURABAYA - Ragam, Regina Pramesti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Title: Use of Acronyms in the Surabaya City Government). This study examines the acronyms used by the Surabaya City Government. There are several objectives to be achieved in this research. The first is to describe the reasons why acronyms are widely used in the Surabaya City Government environment to describe the effect of using acronyms for smooth communication in the Surabaya City Government environment. The second is to describe the patterns of acronym formation in the Surabaya City Government. The third describes the existing acronyms whether they are in accordance with the Indonesian Phonotactic rules. The data in this study were collected by using a questionnaire and the observation method. The results show that there are two reasons why the Surabaya City Government uses a lot of acronyms. There are two reasons that are expected from the use of acronyms, but in fact the use of acronyms has an effect. In addition, the acronym found in the Surabaya City Government Environment has three patterns of formation. In connection with the formation of a word acronym pattern, it generally consists of a series of sounds with the status of an Indonesian word. Therefore, acronyms should be in harmony with the Indonesian Phonotactic rules. The phonotactics used in this study include the distribution of vowels, distribution of consonants and clusters. Keywords: acronyms, Surabaya City Government, phonotactics, structuring patterns.